'Commodifying institutions': vertical disintegration and institutional change in German labour relations. (February 2014) - Holst, Hajo
The article analyses the impact of vertical disintegration on German labour relations. Previous research argued that the proliferation of outsourcing, divestment and non-standard employment results in a 'dualism' between a core of secure workplaces and a growing fringe of precarious jobs. Evidence from two key sectors, metalworking and telecommunications, however, suggest that this clear-cut division is replaced by a fragmented landscape of labour relations. In terms of institutional change, the analysis reveals a specific form of incremental transformative change, namely a shift in the meaning of formally stable legal-political institutions. Even in the allegedly stable core areas, the institutions of labour relations are gradually transformed from market-constituting institutions to market-dependent variables. Vertical disintegration plays an important role in this process of institutional commodification. It not only moves the core–periphery boundary; it is also deployed to subjugate collective bargaining, workplace co-determination and the utilization of labour law to firm-level economic calculations.